Q: What is the answer to 7p plus 2?

Write your answer...

Submit

Related questions

4p + 9 + (-7p) + 2 = 4p - 7p + 9 + 2 = -3p + 11

4p + 9 - 7p + 2 4p - 7p + 9 + 2 p(4 - 7) + 9 + 2 -3p + 11

7p + 2 = 5p + 8 7p - 5p = 8 - 2 2p = 6 p = 3

4p+9-7p+2 -3p+11 p = 11/3

Collect like terms together: 4p + 9 + 7p + 2 = (4p + 7p) + (9 + 2) = (4 + 7)p + 11 = 11p + 11 = 11(p + 1)

6nx + 7p - 14p + 2nx + 6x = 8nx - 7p + 6x

11p+11

2p+7p = 9p simplified

4(7p + 3q - 2)

it is -7p + 32: exactly as in the question!

5p + 15p + 7p = 27p 5p - 15p + 7p = -3p 5p x 15p + 7p = 75p2 + 7p 5p/15p + 7p = 7p + 1/3

It is: 11p+11 simplified

8p+5 = 11+7p= 8p-7p = 11-5p = 6

14 + 6p = 6 + 7p 8 = p

If you mean: 7p-3p+4-2 = 2p-1+10 => 4p+2 = 2p+9 => 2p = 7 Therefore: p = 7/2 => p = 3.5

7p+5t

-7p + 5r - 6p + 3r = -7p - 6p + 5r + 3r = -(7 + 6)p + (5 + 3)r = -13p + 8r

-3p

15 + 3 = 7p - 4p ie 18 = 3p so p = 6

5p-7q

p=-3

8m(4 + 7p)

(3q + 2p)(9q + 7p)

7p-10p = -3

5p + 4y

Study guides